Mental health inequalities in times of crisis: evolution between 2005 and 2021 among the Spanish salaried population. Issue 1 (7th November 2022) - Esteve-Matalí, Laura; Llorens-Serrano, Clara; Alonso, Jordi; Vilagut, Gemma; Moncada, Salvador; Navarro-Giné, Albert
Abstract : Background: Studying the working population's mental health in times of crisis (such as the 2008 recession or the COVID-19 pandemic) is very relevant. This study aims to assess the prevalence of poor mental health among the Spanish salaried population, according to the labour market inequality axes (2005–2021). Methods: Repeated cross-sectional study by comparing different surveys from 2005, 2010, 2016 and 2021 on workers residing in Spain who had been working in a salaried job during the week preceding the survey. n=7197 (2005), n=4985 (2010), n=1807 (2016) and n=18 870 (2021). Outcome variable: poor mental health (Mental Health Inventory of the 36-item Short Form Health Survey scale). Explanatory variables: gender, age, occupational class and type of contract. Prevalence of poor mental health was estimated for each year by means of logistic regression models with robust clustered SEs, stratifying by the explanatory variables. Additionally, prevalence ratios (PR) were estimated by means of robust Poisson regression models to assess differences between the explanatory variables' categories. All analyses were weighted to address unrepresentativeness. Results: Poor mental health significantly increased in 2021 (55.92%), compared with the previous years of study (15%–17.72%). Additionally, pattern changes were identified on inequality axes in 2021, with better mental health status among older workers (oldest group PR: 0.76; 95% CI 0.71 to 0.8) and permanent workers (PR: 0.9; 95% CI 0.85 to 0.94). Conclusion: This study shows a steep worsening of mental health among the salaried population in 2021 compared with previous periods. In 2021, health inequalities have apparently narrowed, although not by improving the disadvantaged groups' mental health but by worsening the typically advantaged groups' mental health.